Study to evaluate the abrasive wear resistant behavior of materials coated with Fe-Cr-Si-C - Yaz, M.; Yilmaz, S. O.; Teker, T. (Redakcia Kovove Materialy, 2011)
Surfaces that are coated with steel are considered useful for grinding and milling applications based on their ability to resist abrasions. In the present study, the microstructures of hypoeutectic, eutectic, and hypereutectic compositions in 10-20 wt.% chromium (Cr) samples were studied with respect to the micro-structural transitions of the coatings and several other processing parameters. In addition, tests were conducted in order to analyze the influence of the microstructure of the coated surfaces on the capacity of the hypoeutectic, eutectic, and hypereutectic Cr-enriched microstructures of the samples coated with 10-20 wt.% Cr alloy to resist wear. Consequently, it was found that based on the presence of an austenitic matrix within them, the coated regions effectively resisted abrasions.
Keywords: coating; gas tungsten arc welding (GTAW); surface modification; chromium